Deteksi Wajah Berbasis Segmentasi Model Warna Menggunakan Template Matching Pada Objek Bergerak - Yusron Rijal; Riza Dhian Ariefianto (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2008)
Digital image face detection had been developing so much in this last decade. The searching for the bestmethod is still walking until today. This face detection research is using color model based segmentation methodcombined with template matching. There are 4 main process in this research. First, motion detection is used tominimize the size of the image by subtracting image n with image n+m. Then, by using YCbCr color model basedsegmentation, the image is separated by skin color area and non-skin color area. Third, is to reduce the noise byusing the blurring way and by filtering its wide. The last one is matching the area that last with template that hasbeen prepared to detect which area is face. The result of the research, from 217 images and 10 videos , showsthat this method reach up to 70,5% face detection accuration procentage.Keywords : Face Detection, Skin Color Segmentation, Noise Reducing, Template Matching.